Electrochemical Synthesis of Purine Alkaloid Metabolites from Caffeine - Ridho Asra; Alan M. Jones (ChemElectroChem)
Abstract The development of electrochemical approaches to the valorization of abundant natural products into high value medications and metabolites is of pharmaceutical interest. In this study, we explored the electrosynthetic behavior of the abundant legal psychoactive, caffeine, a representative member of the purine alkaloid class. Initial screening of the cyclic voltammetric behavior of eleven exemplar purine alkaloids revealed a structure electroactivity relationship (SeAR) for determining the initial oxidation site of caffeine. Optimization of the current controlled electrochemical (CCE) reaction enabled the dialing‐in/out of differential oxidative metabolic products using both undivided and divided cells. Sequential desmethylation around the purine ring was observed both by isolation and comparison to authentic metabolite reference standards via HPLC measurements. Amide, imide, and a novel N‐methyl heteroaryl oxidation mechanism were observed. Tractable quantities of the high‐value medication, theophylline, and the dietary supplement, paraxanthine, were isolated in 17 % and 8 % b.r.s.m. This approach offers a marked improvement compared to the best‐in‐class techniques (chemical 0.8 % and enzymatic 0.97 % yields) and may have potential in other natural product and drug discovery settings to prepare valuable metabolites.